Enantioselective syntheses and application of 4-epi-galiellalactone and the corresponding activity-based probe: from strained bicycles to strained tricycles. Issue 7 (5th September 2018) - Lu, Yandong; Zhao, Shan; Zhou, Shijie; Chen, Si-Cong; Luo, Tuoping
Abstract : Efficient syntheses of 4- epi -galiellalactone and the corresponding activity-based probe enabled chemoproteomic studies to reveal the biological targets. Abstract : The [6, 5, 5] tricyclic fungal metabolite galiellalactone is a Michael acceptor that has been demonstrated to be a covalent inhibitor for Signal Transducer and Activator of Transcription 3 (STAT3). Recognizing the ring strain associated with the skeleton of this natural product, we utilized 1 R -5 S -bicyclo[3.1.0]hexan-2-one as the starting material and developed two novel approaches to accomplish the enantioselective total synthesis of the C4 epimer of galiellalactone in 5 and 7 steps, respectively, which capitalized on an efficient radical cyclization/fragmentation cascade reaction. Furthermore, an activity-based probe of 4- epi -galiellalactone with a terminal alkyne tag was successfully prepared to enable the experiments of activity-based protein profiling (ABPP). Through western blot and proteomic analysis, we not only confirmed the known target STAT3, but also identified a new target protein ataxin-7, which formed a covalent bond with the probe in intact cells via the Cys-129 residue.